"Coming home to myself": A qualitative analysis of therapists' experience and interventions following training in theater improvisation skills. (April 2017) - Romanelli, Assael; Tishby, Orya; Moran, Galia S.
Highlights: Improvisation skills training is connected to an increase in therapeutic presence. Alumni report increased mindfulness, boldness, and self-disclosure in their work. Training effects' related to the therapeutic charisma and therapeutic impact. Improvisation training can help enhance relationship skills of therapists. Abstract: Clinical research suggests that therapists in their sessions be spontaneous, open to self and others on a moment-to-moment awareness, and to communicate in an honest and direct manner. These relationship skills can be difficult to teach. Theater improvisation skills increase spontaneity, animation and co-creation with the other, as well as enhance immediacy skills. This pilot study examines the effects of theater improvisation skills training on therapists' perceptions of therapy and their subsequent clinical interventions. This paper presents the qualitative arm of a larger mixed-methods study of therapists who participated in a 3-month theater improvisational skills course, given at a clinical graduate program in social work in a major university in Israel. Seventeen course graduates were interviewed regarding the training and its effects on their clinical work. Qualitative analysis shows that following the course participants experienced higher levels of therapeutic presence in terms of use of intuition, awareness in the here-and-now and mindfulness. In addition, reports of increased levels of animation, boldness and self-disclosure are discussed in relation to therapeutic charisma and therapeutic impact. Results suggest that training in theater improvisation skills constitutes an important addition to traditional training in relationship skills in psychotherapy. Implications for therapist training are also discussed.